Teaching the reading of heritage books using the selective method at the Darul Ulum Banyuanyar Pemekasan - Ma'sud, Ahmad Tarajjil; Muchit, Romli A.; Jazilah, Ela (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2023)
This study aims to explain the learning process of Islamic heritage books with this eclectic method which is applied at the Darul Ulum Banyuanyar Islamic Boarding School Pamekasan is planning implementing and evaluating in process is carried out. This research method uses a descriptive qualitative approach, with data collection methods in the form of observation, interviews and observations. Then, the collected data were analyzed using data analysis techniques in the form of data collection, data reduction, data display, and conclusion/verification. The validity of this research data uses the technique of triangulation method and member check. The results of this study are: (a) Learning planning starting with carrying out tests, determining mentors, conducting training for mentors, carrying out tests for mentors, and forming groups according to initial test results. And the media used is, question and answer guidebooks, whiteboards, markers, erasers, projectors, sound systems, and microphones, (b) The implementation is carried out in a week of 5 days, giving value to sentences read and translated using Madurese language, and (c) Evaluation of learning is an oral test which is carried out every time you complete 10 material numbers. المراجع أبو جعفر محمد ابن جرير الطبري. جامع البيان عن تأويل آي القرآن. بيروت لبنان: دار الفكر أحسن.